2020
DOI: 10.1186/s12905-020-01078-3
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of breastfeeding duration with joint pain and knee osteoarthritis in middle-aged Korean women: a cross-sectional study using the Korea National Health and Nutrition Examination Survey

Abstract: Background The effect of joint health on the quality of life of middle-aged and older women is becoming more widely recognized with the aging of the world’s population. However, the association of long-term breastfeeding with joint pain and knee osteoarthritis has not been fully examined. The aim of this study was to determine the association of prior breastfeeding duration with current joint pain and knee osteoarthritis in middle-aged Korean women. Methods This cross-sectional study was conducted among 3454… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…1.01-4.64) [21]. In study using Women's Health Initiative, among postmenopausal women aged 50, self-reported osteoarthritis of those who breastfed for 1-3 months, 4-6 months were higher risk than who non breastfed(OR: 1.026, 95% CI: 1.017-1.034, OR: 1.015, 95% CI: 1.006-1.025, respectively) [22].…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…1.01-4.64) [21]. In study using Women's Health Initiative, among postmenopausal women aged 50, self-reported osteoarthritis of those who breastfed for 1-3 months, 4-6 months were higher risk than who non breastfed(OR: 1.026, 95% CI: 1.017-1.034, OR: 1.015, 95% CI: 1.006-1.025, respectively) [22].…”
Section: Discussionmentioning
confidence: 98%
“…American women over 50 years of age with a history of breastfeeding were found to have a higher risk of developing osteoarthritis than women who did not breastfeed (OR, 1.21; 95% CI, 1.05 to 1.40) [ 21 ]. Among Korean women over 50 years of age, the prevalence of knee osteoarthritis diagnosed radiologically among those who had breastfed for 25-48 months was higher than that among non-breastfeeding women (OR, 2.30; 95% CI, 1.09 to 4.86); for those with a breastfeeding duration of more than 48 months, the prevalence of knee osteoarthritis was higher than that in non-breastfeeding women (OR, 2.17; 95% CI, 1.01 to 4.64) [ 22 ]. In a study using Women’s Health Initiative data, among postmenopausal women aged ≥ 50 years, those who had breastfed for 1-3 months (OR, 1.026; 95% CI, 1.017 to 1.034) or 4-6 months (OR, 1.015; 95% CI, 1.006 to 1.025) were more likely to self-report osteoarthritis than those who had never breastfed [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation